Retrospective study of psoriasis in people living with HIV: Thailand’s experience - Chayada Chaiyabutr (2022)
Psoriasis in people living with HIV (PLHIV) has been reported as having particular clinical characteristics. However, most of the source data was derived from descriptive studies in Europe and the USA. This study was conducted to compare the characteristics of psoriasis in PLHIV to general psoriasis patients. We retrospectively reviewed the records of 73 cases of psoriasis in PLHIV and of 232 general psoriasis patients who visited a psoriasis clinic in Bangkok, Thailand. Psoriasis in PLHIV predominated in males (78.1%), with an older age of onset, significantly lower rates of nail involvement and psoriatic arthritis, but higher rates of co-infectious diseases than for general psoriasis patients. A low nadir CD4 T-cell count (<100 cells/μl) and CD4 T-cell count at psoriasis diagnosis were associated with a high body surface area (BSA) involvement. The mean BSA involvement in PLHIV was 24. Although 64.4% (47/73) of the PLHIV had moderate-to-high psoriasis severity, 29.8% of those (14/47) only received topical treatment. Acitretin was the most common drug used. Other therapies were rarely used, and no biologics were administered. In conclusion, psoriasis in PLHIV has several clinical features that differ from general psoriasis. PLHIV tend to receive substandard care for psoriasis, even in upper-middle-income countries.